Exploring rural Chinese teachers' attitudes towards wellbeing: Qualitative findings from appreciative semi-structured interviews. Issue 1 (6th April 2022) - Cui, Bo; White, Mathew A.; McCallum, Faye
Teachers in rural China are considered disadvantaged compared to their urban counterparts on several measures, including working conditions, remuneration, and access to professional development opportunities. We argue that teacher wellbeing plays a crucial role in teacher quality because quality teachers require optimal functioning and wellbeing to teach well. This study reports on the qualitative element of an exploratory sequential mixed-methods research design investigating Chinese rural teachers' attitudes towards wellbeing. The results of this study confirmed that remuneration, access to professional development opportunities and social status of rural teachers are behind those of urban teachers in China. However, several rural teachers excelled in the profession, showing a passion for teaching that transformed the lives of rural students. This study discovered a gap in the current research on the wellbeing of rural teachers in China and suggested that policymakers should promote the unique positive aspects of rurality, including teachers' passion for optimal outcomes for their students, rather than focussing on the negative aspects of rurality.